Histological Studies of Preen Gland of Some Pet Birds - Kushwaha, Pramod Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
Preen gland is also known as uropygial gland or oil gland. It is bilobate sebaceous gland possessed by the majority of birds. It is located dorsally at the base of tail between the fourth caudal vertebra and pygostyle and is greatly variable in both shape and size. Most birds preen by rubbing their bill and head over the preen gland pore and then rubbing the accumulated oil over the feathers of the body and wings and the skin of the legs and feet. Birds also distribute the oil over the plumage. During distribute the oil over the plumage. During preening, birds gather oily secretions that contain diester waxes from their oil glands. Preening is a bird’s way of grooming it’s feathers to keep them in the best condition.